A Phenomenological Study of Farmers' Farm Business Diversification Decisions in Sidomulyo Village, Batu - Mahdalena Mahdalena; Ahmad Suhaimi (Journal of Agribusiness and Natural Resources, 2025)
Despite a high awareness of its benefits, the adoption rate of farm business diversification in Indonesia remains low, indicating a complex decision-making process beyond simple economic calculation. This study explores the lived experiences of farmers in Sidomulyo Village, Batu City, to understand the perspectives, driving factors, and obstacles influencing their diversification decisions. Employing a qualitative phenomenological approach, the research involved in-depth interviews with 23 informants, including farmers practicing various forms of diversification, non-diversifiers, and key village stakeholders. The findings reveal that diversification decisions are a non-linear social journey, triggered by critical moments such as crop failure, and mediated by learning from trusted “innovator farmer” role models. Social capital within farmer groups functions paradoxically as both an enabler, through information exchange and safety nets, and a constraint, through conformity pressures. Farmers demonstrate creative agency by utilizing traditional practices like gotong royong to overcome structural limitations in infrastructure and market access, yet remain constrained by them. Crucially, the meaning of diversification extends beyond income stability to encompass identity as innovators, a strategy for intergenerational succession, and nascent ecological awareness, with women often acting as the hidden drivers of change. This research critiques top-down extension models, recommending policies that facilitate social learning, strengthen both bonding and bridging social capital, and address gendered constraints to foster more resilient and sustainable agricultural livelihoods.